Role of DECT-Based Imaging Biomarkers and Machine Learning to Predict Renal Cell Carcinoma Subtypes - Neha Baijal; Amit Gupta; Sanil Garg; Neel Yadav; Rohan R. Dhanakshirur; Kshitiz Jain; Chandan J. Das (Indian Journal of Radiology and Imaging)
Objective The aim of the study was to assess and compare dual-energy CT (DECT) based quantitative parameters to differentiate between clear cell renal cell carcinoma (ccRCC) and non-ccRCC.